Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Komunikasi dan Hasil Belajar Kognitif Siswa SMAN 1 Ngemplak pada Materi Sistem Peredaran Darah - Rahma Sari, Rosita; Irawati, Hani (Syntax Literate, 2025)
This research is motivated by the communication skills and cognitive learning outcomes of students who are still low in the material of the circulatory system. Communication skills are very important to be taught to students, because they can help students obtain information provided by teachers in the form of learning materials. This study was conducted with the aim of determining the influence of the problem-based learning model on communication skills and cognitive learning outcomes of circulatory system materials in SMA N 1 Ngemplak. This quasi-experimental research uses a pretest-posttest design of the grub control. The population in this study is students in grades XI MIPA 1 and XI MIPA 2 SMA N 1 Ngemplak. The sampling technique used random sampling with class XI MIPA 1 as the experimental class and class XI MIPA 2 as the control class. Collection techniques with tests and observations. The instruments used were pretest and posttest questions in the form of multiple choice and observation sheets. The data analysis technique is with prerequisite tests in the form of normality tests, and homogeneity tests. Hypothesis testing using the Mann Whitney U-Test. The results of the study show that (1) There is an influence of the problem-based learning model on students' communication skills on circulatory system materials. (2) There is an influence of the problem-based learning model on the cognitive learning outcomes of students in circulatory system materials. From the results of the Mann-Whitney U test, the Asymp value. Sig (2-tailed) is 0.002<0.05.